Hydraulic fluids - Hodges, Peter Keith Brian (Knovel Library, 1996)
* Reviews the development of modern hydraulic fluids * Discusses the application and selection of hydraulic fluids through the investigation of their physical and chemical properties related to the operational requirements. * Offers guidance on suitable maintenance routines Since the first use of water as a hydraulic medium in the late 18th century, hydraulics has become an indispensable discipline of engineering science. Enormous technological advances have been made in the intervening years, but this has not been reflected in the available literature on the numerous fluids involved. Based on 40 years of experience with Shell in Norway, this reference text brings together a comprehensive coverage of the behaviour and selection of hydraulic fluids. It includes a full analysis of recent advances in synthetic oils - media which will inevitably become more dominant as natural products become more scarce. Hydraulic Fluids provides an overview that both students and professionals involved with hydraulics, whether concerned with the mechanical components or system design or selection and maintenance of the fluids themselves, will refer to again and again as it provides relevant information on all the major hydraulic fluids in a single volume